To Know or Not to Know, That Is the Question: Knowledge and politics - Romero, Gustavo (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2024)
Book review. SCHEALL, Scott. F. A. Hayek and the Epistemology of Politics: The Curious Task of Economics. London: Routledge, 2020. xiv + 200 p.